Epoxyeicosatrienoic Acid-Based Therapy Attenuates the Progression of Postischemic Heart Failure in Normotensive Sprague-Dawley but Not in Hypertensive Ren-2 Transgenic Rats - Hrdlička, Jaroslav; Neckář, Jan; Papoušek, František; Husková, Zuzana; Kikerlová, Soňa; Vaňourková, Zdenka; Vernerová, Zdenka; Akat, Firat; Vašinová, Jana; Hammock, Bruce D.; Hwang, Sung Hee; Imig, John D.; et al. (Frontiers in Pharmacology, 2019)
Epoxyeicosatrienoic acids (EETs) and their analogues have been identified as potent antihypertensive compounds with cardio- and renoprotective actions. Here, we examined the effect of EET-A, an orally active EET analogue, and c-AUCB, an inhibitor of the EETs degrading enzyme soluble epoxide hydrolase, on the progression of post-myocardial infarction (MI) heart failure (HF) in normotensive Hannover Sprague-Dawley (HanSD) and in heterozygous Ren-2 transgenic rats (TGR) with angiotensin II-dependent hypertension. Adult male rats (12 wks old) were subjected to 60-minute left anterior descending coronary artery occlusion or sham (non-MI) operation. Animals were treated with EET-A and c-AUCB (10 and 1 mg/kg/day, respectively) in drinking water, given alone or combined for 5 weeks starting 24 h after MI induction. Left ventricle (LV) function and geometry were assessed by echocardiography before MI and during the progression of HF. At the end of the study, LV function was determined by catheterization and tissue samples were collected. Ischemic mortality due to the incidence of sustained ventricular fibrillation was significantly higher in TGR than in HanSD rats (35.4% and 17.7%, respectively). MI-induced HF markedly increased LV end-diastolic pressure (Ped) and reduced fractional shortening (FS) and the peak rate of pressure development [(dP/dt)max] in untreated HanSD compared to sham (non-MI) group [Ped: 30.5±3.3 vs. 9.7±1.3 mmHg; FS: 11.1±1.0 vs. 40.8±0.5%; (dP/dt)max: 3890±291 vs. 5947±309 mmHg/s]. EET-A and c-AUCB, given alone, tended to improve LV function parameters in HanSD rats. Their combination amplified the cardioprotective effect of single therapy and reached significant differences compared to untreated HanSD controls [Ped: 19.4±2.2 mmHg; FS: 14.9±1.0%; (dP/dt)max: 5278±255 mmHg/s]. In TGR, MI resulted in the impairment of LV function like HanSD rats. All treatments reduced the increased level of kidney injury markers in TGR compared to untreated MI group, but neither single nor combined EET-based therapy improved LV function. Our results indicate that EET-based therapy attenuates the progression of post-MI HF in HanSD, but not in TGR, even though they exhibited renoprotective action in TGR hypertensive rats.